Women's Language Features Used by a Woman Who Masquerades as a Man in Mulan (2020) Movie - Natasha Ayalus Yoan Yola Yolanda; Barli Bram (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
This paper aimed to explore the use of women’s language features by a woman character who masquerades as a man in Mulan (2020) movie. Two research questions were formulated. First, what women's language features are used by the character Mulan in Mulan (2020) movie? Second, does Mulan still use the women’s language features while she masquerades as a man? This study was qualitative research and used a document analysis to analyze the data. Two observation checklist tables and a frequency comparison table were used to help the researchers to categorize the data for interpretation. The results that showed the percentage of the women’s language features from Mulan’s utterances when she played a role as a woman was 83.33% and then decreased to 58.82% when she played a role as a man. The results also showed that the gender roles in society take part in forming someone’s speech. The decreasing point proved that playing a role as a man helped Mulan to feel more confident to state her ideas in society.